2019
DOI: 10.1101/791954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence-Dependent Dynamics of Synthetic and Endogenous RSSs in V(D)J Recombination

Abstract: Developing lymphocytes in the immune system of jawed vertebrates assemble antigen-receptor genes by undergoing large-scale reorganization of spatially separated V, D, and J gene segments through a process known as V(D)J recombination. The RAG protein initiates this process by binding and cutting recombination signal sequences (RSSs) composed of conserved heptamer and nonamer sequences flanking less well-conserved 12-or 23-bp spacers. Little quantitative information is known about the contributions of individua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Recently, a research reported cryoelectron microscopy structures of synaptic RAG complexes at up to 3.4 Å resolution, which reveal a closed conformation with base flipping and base-specific recognition of RSSs (Ru et al, 2015). Another study employed a single-molecule method to track the RAG-RSS interaction, which can provide a relatived complete kinetic description of the initial phases of V(D)J recombination (Hirokawa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a research reported cryoelectron microscopy structures of synaptic RAG complexes at up to 3.4 Å resolution, which reveal a closed conformation with base flipping and base-specific recognition of RSSs (Ru et al, 2015). Another study employed a single-molecule method to track the RAG-RSS interaction, which can provide a relatived complete kinetic description of the initial phases of V(D)J recombination (Hirokawa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…RAG recognizes conserved recombination signal sequences (RSSs) positioned adjacent to V, D, and J gene segments. A bona fide RSS contains a conserved palindromic heptamer (consensus 5′-CACAGTG) and A-rich nonamer (consensus 5′-ACAAAAACC) separated by a degenerate spacer of either 12 or 23 base pairs (Hirokawa, et al,2020;Schatz and Ji,2011). The process of efficient recombination is contingent upon the presence of recombination signal sequences (RSSs) with differing spacer lengths, as dictated by the "12/23 rule" (Banerjee and Schatz,2014;Eastman, et al,1996;Shi, et al,2020).…”
Section: Introductionmentioning
confidence: 99%